Imaging and Outcomes for a New Entity: Low-Grade Sinonasal Sarcoma with Neural and Myogenic Features - Cannon, Richard B.; Wiggins, Richard H., III; Witt, Benjamin L.; Dundar, Yusuf; Johnston, Tawni M.; Hunt, Jason P. (Journal of Neurological Surgery Reports, 2017)
Objectives Low-grade sinonasal sarcoma with neural and myogenic features (LGSSNMF) is a new, rare tumor. Our goal is to describe the imaging characteristics and surgical outcomes of this unique skull base malignancy.Design Retrospective case series.Setting Academic medical center.Participants There were three patients who met inclusion criteria with a confirmed LGSSNMF.Main Outcome Measures Imaging and histopathological characteristics, treatments, survival and recurrence outcomes, complications, morbidity, and mortality.Results Patients presented with diplopia, facial discomfort, a supraorbital mass, and nasal obstruction. Magnetic resonance imaging and computed tomography imaging in all cases showed an enhancing sinonasal mass with associated hyperostotic bone formation that involved the frontal sinus, invaded the lamina papyracea and anterior skull base, and had intracranial extension. One patient underwent a purely endoscopic surgical resection and the second underwent a craniofacial resection, while the last is pending treatment. All patients recovered well, without morbidity or long-term complications, and are currently without evidence of disease (mean follow-up of 2.1 years). One patient recurred after 17 months and underwent a repeat endoscopic skull base and dural resection.Conclusions The surgical outcomes and imaging of this unique, locally aggressive skull base tumor are characterized.
Keywords: low-grade sinonasal sarcoma with neural and myogenic features; skull base malignancy; imaging characteristics; surgical outcomes; hyperostotic bone formation; locally aggressive; sinonasal sarcoma